Social Crime and Social Instability in Nigeria: A Threat to National Security and Job Opportunities. A Study of the Menace of Kidnapping in South-South Region - Ijeoma Uchenna Camenus; Anasieze Ifeoma Joy; Ugwu Cynthia Chibugo (Journal of Current Research and Studies, 2025)
Evidently, South-South region of Nigeria is one of the six geo-political zones in Nigeria, consisting of the following six States: Akwa-Ibom, Bayelsa, Cross River, Delta, Edo and Rivers states. The recent surge in kidnapping has seen prominent members of the society becoming victims of abductions, it appears that armed robbers, fraudsters and small-time crooks have since dumped their different trades and moved on to the more lucrative business of kidnapping. This development has adversely affected security and employments in this region. Not only Nigerians, but also the international community, are concerned and perplexed by the major impact of kidnapping and other related crimes. This has increased the fear of outsiders, particularly multinational investors, putting the foundations of economic development in jeopardy. The total impact has exacerbated the labor market crisis, resulting in thousands of job losses and workforce displacement from the affected areas. This research examines the rising wave of crime and its effect to the Nigerian labor market. According to this research, the current wave of kidnappings has exacerbated widespread unemployment, aggravating an already deteriorating labor market and creating an unfavorable atmosphere for economic development. It is recommended, among other things, that the government should create jobs for unemployed youths while also providing skills development training, as idleness is the mother of evil thoughts, evil plans, and evil actions among Nigerian youths; and that the federal and state governments should properly recruit, equip and deploy forest guards into our forests, which are serving as safe havens for kidnappers, in order to combat the menace. This would provide suggestions on how to combat this wave of crime and extend the labor market to accommodate these restless adolescents who are the main perpetrators of this crime.